2014
DOI: 10.5194/se-5-499-2014
|View full text |Cite
|
Sign up to set email alerts
|

Crop residue decomposition in Minnesota biochar-amended plots

Abstract: Abstract. Impacts of biochar application at laboratory scales are routinely studied, but impacts of biochar application on decomposition of crop residues at field scales have not been widely addressed. The priming or hindrance of crop residue decomposition could have a cascading impact on soil processes, particularly those influencing nutrient availability. Our objectives were to evaluate biochar effects on field decomposition of crop residue, using plots that were amended with biochars made from different pla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…From Table 3, biochar from corncob had significantly high ash content (23.4%). Ash from organic waste is rich in potassium, calcium and magnesium which are suitable for plant growth (Weyers and Spokas 2014). The ash content in the biochar increased with temperature with a positive significant correlation coefficient of 0.439 * at P < 0.01 (Table 4).…”
Section: Efficiency Of the Pyrolysis Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…From Table 3, biochar from corncob had significantly high ash content (23.4%). Ash from organic waste is rich in potassium, calcium and magnesium which are suitable for plant growth (Weyers and Spokas 2014). The ash content in the biochar increased with temperature with a positive significant correlation coefficient of 0.439 * at P < 0.01 (Table 4).…”
Section: Efficiency Of the Pyrolysis Unitmentioning
confidence: 99%
“…When added to acidic soils, biochar like other organic fertilizers (green manure, animal manure and compost) influences soil characteristics such as soil pH and bulk density (Djousse et al 2016;Siamak et al 2017). Studies have shown that adding biochar to soils increases soil organic matter (SOM) and organic carbon which then enhances nutrient supply to plants and promote plant growth (Weyers and Spokas 2014;Dotaniya et al 2016). Growing interest in biochar has also been associated with its carbon sequestration ability, to reduce CO 2 emissions by slowing down the return of photosynthetically fixed carbon to the atmosphere (Enders et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The variables that influence C sequestration and consequently the SOC pool include climate, soil physical and chemical characteristics, land management, and the input and decomposition of plant residues, including leaves, roots, and root exudates. (Cely et al, 2014;Parras-Alcántara & Lozano-García, 2014;Srinivasarao et al, 2014;Weyers & Spokas, 2014;Kaleeem Abbasi et al, 2015). The SOC pool can generally be increased by agricultural management that increases litter input and reduces tillage intensity (Bell et al, 2003;Alvaro-Fuentes et al, 2009a;Carr et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The dominant approaches of many suggested practices are still purely biophysical (e.g. García-Orenes et al, 2012;Weyers and Spokas, 2014;Sadeghi et al, 2015;Cerdà et al, 2015). However, the livelihood approach provides the perspective that natural resource degradation should be tackled in a wider manner than only a cause-and-effect logic due to a linear ecological process (Gharibvand et al, 2015).…”
Section: A Step Towards a Multidimensional Protocol To Combat Desertimentioning
confidence: 99%